Pengaruh Kualitas Website Dan Harga Terhadap Kepuasan Konsumen Shopee (Studi Kasus Mahasiswa FEB Unisma) - M. Syahrul Gunawan; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe results of this study indicate that website quality and price simultaneously have a significant effect on Shopee consumer satisfaction for FEB UNISMA students. Website quality partially has a positive and significant effect on Shopee consumer satisfaction, which means that if the quality of the website is getting better, customer satisfaction will increase. Price has partially a significant positive effect on consumer satisfaction, which means that the price will affect consumer satisfaction if the price set by Shopee is affordable and in accordance with the quality of the product. Keywords: Customer Satisfaction, Website Quality, Price